Three new species of Kynotus from the Central Highlands of Madagascar (Clitellata, Megadrili) - Csuzdi, Csaba; Razafindrakoto, Malalatiana; Hong, Yong (European Journal of Taxonomy, 2017)
The earthworm fauna of Madagascar is scarcely known. A recently launched exploration of the soil fauna (“Global Change and Soil Macrofauna Diversity in Madagascar”) resulted in the discovery of six new earthworm species belonging to the Malagasy endemic family Kynotidae. The success of the collecting campaign carried out between 2008 and 2011 inspired a new exploration of the earthworm fauna across the Central Highland Region of the island in the spring of 2015. During this expedition, two new species of Kynotus, K. ankisiranus sp. nov. and K. voimmanus sp. nov., were discovered. Barcoding of the recently collected species of Kynotus revealed that the unpigmented worms referred previously to K. alaotranus Michaelsen, 1897 also represented a new, still undescribed species, K. blancharti sp. nov.